Luteolin Attenuates IL-1β-Induced THP-1 Adhesion to ARPE-19 Cells via Suppression of NF-κB and MAPK Pathways - Wen-Chung Huang; Chian-Jiun Liou; Szu-Chuan Shen; Sindy Hu; Chien-Yu Hsiao; Shu-Ju Wu (Mediators of Inflammation)
Cytokine-induced endothelial dysfunction leads to inflammation and vascular adhesion molecule production in retinal pigment epithelium (RPE) cells. Inflammation is a critical mediator in retinal degeneration (RD) diseases, including age-related macular degeneration (AMD), and RD progression may be prevented through anti-inflammatory activity in RPE cells. The flavonoid polyphenol luteolin (LU) has anti-inflammatory and antidiabetes activities, but its effects regarding retinal protection remain unknown. Here, we examined the ability of luteolin to alleviate markers of inflammation related to RD in cytokine-primed APPE-19 cells. We found that luteolin decreased the levels of interleukin- (IL-) 6, IL-8, soluble intercellular adhesion molecule-1 (sICAM-1), and monocyte chemoattractant protein-1 (MCP-1) and attenuated adherence of the human monocytic leukemia cell line THP-1 to IL-1β-stimulated ARPE-19 cells. Luteolin also increased anti-inflammatory protein heme oxygenase-1 (HO-1) levels. Interestingly, luteolin induced protein kinase B (AKT) phosphorylation, thus inhibiting nuclear factor- (NF-) κB transfer from cytoplasm into the nucleus and suppressing mitogen-activated protein kinase (MAPK) inflammatory pathways. Furthermore, cotreatment with MAPK inhibitors and luteolin decreased inflammatory cytokine and chemokine levels, and further suppressed THP-1 adhesion. Overall, these results provide evidence that luteolin protects ARPE-19 cells from IL-1β-stimulated increases of IL-6, IL-8, sICAM-1, and MCP-1 production by blocking the activation of MAPK and NF-κB signaling pathways, thus ameliorating the inflammatory response.